Histopathological and morphological alterations in salivary gland of House fly Musca domestica L., induced by oral administration Thiamethoxam - Xider, Karim Mohammed (Kurdistan Journal of Applied Research, 2018)
The current work the effect of Actara insecticide belongs to chemical family Neonicotinoid. The active component of thiamethoxam in three concentrations: 0.750 ppm, 1.5 ppm and 2.25ppm on adult house fly salivary glands. Histopathological and morphological effects revealed important alterations produced by this insecticide in histological and morphology of the adult house fly gland tissue categorized by increasing gland duct lumen diameter. These alterations are possibly related with excretion function of salivary gland might be accountable for removing this insecticide. Results show thiamethoxam is a powerful insecticide that performances histologically in salivary glant tissue, triggering alterations in the glands form, cytoplasm with extreme vacuolation ,disruption cell membrane, obvious disorganization tissues cells, terminating in progressive deteriorating phase with changes in nucleus glandular cell’s, such alterations occurred together in its size and form of gland, disintegration of nucleus, and presence of apoptosis(fragmentation) nucleus, accelerating the process of glandular degeneration ,and interfering with feeding process of house fly particularly when the peak concentration of insecticide was used.